Optimal water allocation model based on satisfaction and economic benefits. (1st January 2013) - Divakar, Leena; Babel, Mukand Singh; Perret, Sylvain R.; Gupta, Ashim Das
The study develops an integrated model for allocation of limited available water among competing user sectors. The model comprises a reservoir operation model (ROM) and a water allocation model (WAM). ROM determines the available water, which is used as an input to WAM. Two single and one multi-objective functions are included in the water allocation model. The first single objective function (OF1 ) maximises the satisfaction level in meeting the sectoral water demands and the second single objective function (OF2 ) maximises the net economic benefits from different use sectors. The multi-objective function (OF12 ) is a combination of the first two objectives. An equity concept with the fuzzy (minimum operator) approach is introduced to distribute stress equally among the sectors. The developed model is applied to the Chao Phraya basin in Thailand. The results indicate that the WAM can improve satisfaction levels and net economic returns compared to the current water allocation practices.